Parameters of Mycoplasma pneumoniae infection in Syrian hamsters. - Barile, M F (1988)
An animal model for evaluating the potency of Mycoplasma pneumoniae vaccines was developed with hamsters. Factors that influence hamster infection by M. pneumoniae were defined, and parameters for assessment of intensity of pulmonary disease were established. Colonization of hamster lungs was determined by culture, and intensity of lung disease was assessed histopathologically and expressed numerically as a lung pathological score. Intratracheal inoculation of the challenge was superior to the intranasal or aerosol route for inducing a consistent degree of lung disease. A challenge dose of 10(6) CFU inoculated intratracheally produced lung colonization and significant reproducible lung pathological scores in essentially all unvaccinated animals. The peak of infection, as determined by these criteria, was at about 2 weeks after challenge. Animals over 6 weeks of age were preferable for the test, since younger animals exhibited a lower lung pathological score even though they showed the same degree of lung colonization. The hamster assay developed provides a dependable experimental system for testing the protective potency of M. pneumoniae vaccines.